DEVELOPING STUDENTS’ CRITICAL WRITING SKILLS OF ELEMENTARY SCHOOL BY USING VOCABULARY CHART - Valentin, Cindy Febilia; Muliasari, Desiani Natalina; Ananthia, Winti (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2018)
Abstract:. This article is part of a classroom action research. The paper aims to describe how vocabulary chart is implemented in the writing learning process to develop elementary school students’ English as a Foreign Language (EFL) critical writing skills. The subject of the study is 28 primary school students grade 3 in one of the public schools in Bandung. The Classroom Action Research was employed in the study. The vocabulary chart was used in a 3-cycle lesson consisting of 9 meetings. This paper focuses on the implementation of vocabulary chart in the first cycle. This research is a qualitative research which used classroom observation, documentation, field note and student interview as the instrument of collecting data. After that the obtained data were discussed and processed to be  described, analyzed, and reflected. The data that has been described is then analyzed to  get the findings. In conclusion, the application of the vocabulary chart to develop elementary school students’ EFL critical writing skill can be implemented in two stages, namely: 1) the vocabulary chart delivery, and  2) the using of vocabulary chart in the students’ critical thinking. The study reveals that the vocabulary chart can develop elementary school students’ EFL critical writing skills.Abstrak: Artikel ini adalah bagian dari penelitian tindakan kelas. Makalah ini bertujuan untuk menggambarkan bagaimana bagan kosakata diimplementasikan dalam proses pembelajaran menulis untuk mengembangkan kemampuan menulis kritis bahasa Inggris siswa sebagai Bahasa Asing (EFL). Subyek penelitian adalah 28 siswa sekolah dasar di kelas 3 di salah satu sekolah umum di Bandung. Penelitian Tindakan Kelas digunakan dalam penelitian ini. Bagan kosakata digunakan dalam pelajaran 3-siklus yang terdiri dari 9 pertemuan. Makalah ini berfokus pada penerapan grafik kosakata dalam siklus pertama. Penelitian ini merupakan penelitian kualitatif dengan observasi kelas, dokumentasi, catatan lapangan dan wawancara siswa. Setelah itu data didiskusikan dan diproses dengan cara yang dijelaskan, dianalisis, dan dipantulkan. Data yang telah dijelaskan dianalisis untuk melepaskan temuan. Dalam pengiriman grafik kosakata, dan 2) penggunaan grafik kosakata dalam pemikiran kritis siswa. Studi ini mengungkapkan bahwa grafik kosakata dapat mengembangkan keterampilan menulis kritis EFL siswa sekolah dasar.